The thin blue line meets the big blue sky: perceptions of police legitimacy and public attitudes towards aerial drones - Heen, Miliaikeala S.J. (Criminal justice studies, 2018)
Police departments across the United States are now integrating new visual monitoring technology (e.g. unmanned aerial vehicles [UAVs or ‘drones’], body cameras) into routine police practices. Despite their potential use in multiple areas of proactive and reactive policing, public attitudes toward police use of UAVs, and visual monitoring technology overall, is mixed. As an extension of previous research, the current study uses a national survey to assess how well individuals’ perceptions about police legitimacy, effectiveness, and other criminal justice attitudes predict the level of public receptivity and opposition toward police UAV use in various contexts. The implications of these findings for public policy and law enforcement practices are discussed.